Penerapan Media Pembelajaran Berbasis IT di Pesantren Digital Muhammadiyah At-Tanwir Kabupaten Pasuruan - Fajar Setyadinawan; Faridi Faridi (Jurnal Budi Pekerti Agama Islam, 2024)
The purpose of this research is to find out how the application of IT-based learning media in the Muhammadiyah Digital Islamic Boarding School At-Tanwir, this is motivated by the rapid development of the digital era, and we are all required to play an active role in it so as not to be left behind. With a qualitative research approach and case study research type, researchers want to know in depth about the application of IT-based learning media in this 2-year-old pesantren. The results showed that the application of IT-based learning media was applied to some lessons, because there were some lessons that were practical and memorised. There are also several obstacles ranging from facilities, readiness of students and educators in this learning media.